Learning the Culture of Chinese Indonesian Community through the Documentary Film “Once Upon a Time in Chinatown” - Septerianie Sutandi; Selvia (Jayapangus Press, 2023)
Chinese Indonesian has a very diverse culture. On the other hand, people who are interested in Mandarin and Chinese culture in Indonesia are also increasing. Chinese Indonesian community contributes and has a big role in Indonesian history. The learning media used to study Chinese culture are very diverse, one of which is using documentary films. The purpose of this research is to find out the Chinese Indonesian community values that can be learned by the general public from the film